Internalisasi Nilai Kedisiplinan Santri melalui Kepemimpinan Kiai di Pondok Pesantren - Riadil Jannah (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to describe the process of internalizing student discipline values through kiai leadership at Pondok Pesantren Miftahul Jannah Al-Akramiyah Al-Aziziyah, Tabir District, Merangin Regency. A qualitative method was employed with data collected through observation, interviews, and documentation. Data analysis followed the stages of reduction, presentation, and conclusion drawing. The findings indicate that the internalization of discipline takes place through the kiai’s role as a role model, direct supervision, guidance from teachers (ustaz and ustazah), and the implementation of school regulations supported by an educational reward and punishment system. Student discipline is influenced by internal factors, such as self-awareness, learning goals, and learning interest, as well as external factors, including family, school, and community environments. The study also reveals a gap between formal regulations and actual disciplinary practices, as some students continue to commit violations covertly. The study concludes that the success of discipline building in pesantren depends not only on the kiai’s charisma but also on collective synergy among teachers, administrators, and the pesantren environment. Practically, strengthening collaborative supervision and applying a more humanistic approach are crucial to embed discipline as a pesantren culture.